Innovative Results-Based Approach to Tackling Water Scarcity in São Paulo - Velez, Carlos E.; Tierney, Julia (World Bank, Washington, DC, 2012)
Water is an essential part of supporting sustainable economic growth within a more equitable and inclusive society. Possessing about 14 percent of the world's water, Brazil is rich in water resources, but 70 percent is in the Amazon River and only 1.6 percent in the State of Sao Paulo, where 25 percent of the population resides and 33 percent of the country's gross domestic product (GDP) is generated. The Bank has recently approved the innovative Sao Paulo Water Recovery Project (REAGUA) which adopts output-based financing to tackle water scarcity. This is the first Bank-financed project in the water supply and sanitation (WSS) sector to implement comprehensive results based scheme. Its objective is to increase clean water availability in São Paulo but its lessons could be applied worldwide.